ROMAN V. VYNNYCHENKO “NOTES OF THE KIRPAT MEPHISYOPHELES” THROUGH THE PRISM OF CINEMATOGRAPHIC MEANS OF ARTISTIC CREATON - Fedoriv, M. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article analyzes V. Vynnychenko’s novel «Notes of Kirpat Mephistopheles» and its screen version, created by directors U. Lyashenko and P. Movchan, some aspects of the literary work content transformation and its transference to the cinema format.